Pengaruh Kecerdasan Emosional Dan Minat Belajar Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Metri Apriyana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
This Research Aims to Find Out The Impact of Emotional Questions and The Interest of Learning Social Sciences Toward Students In South Jakarta. Using a correlation method, this research apllies regression techniques and survey approach. Researcher tooks 600 students as population, consist of 265 Junior High School and 73 Junior High School students, by using multiple choice questionaries as the data collection method. This study has proven that emotional questions and interest of learning simultaneously affect students achievement on social sciences. Keywords : Emotional Questions, Interest of Learning, Student Achievment, Social Sciences